Mental Health at Workplace: A Bibliometric Analysis of Literature from Canada (European Journal of Behavioral Sciences, 2020)
The purpose of this paper is to identify and review the research themes in the area of mental health in workplace. I conduct a bibliometric analysis of 219 peer-reviewed articles specific to research conducted in Canada. The articles are extracted from EBSCO using the key words “mental health” and “workplace” and published between the years 2000 and 2020. A qualitative research technique – ‘co-occurrence of key words’ is used to identify the most relevant key words in the theoretical corpus of 219 articles. Most frequently occurring words are clustered together forming a research theme. Five research themes- healthcare management, organizational context and support, psychological issues, methodology & research design, and Participants are identified. This research makes a significant academic contribution in providing directions for future research on the topic of mental health in organizations. From the practitioner viewpoint, it draws the attention of healthcare professionals to some of the more recent practices in organizations that address the important issue of mental health.